PENGARUH LITERASI KEUANGAN SYARIAH TERHADAP PENGGUNAAN PEMBIAYAAN MIKRO SYARIAH OLEH PELAKU USAHA NON-MUSLIM DI KECAMATAN PANGARIBUAN, KABUPATEN TAPANULI UTARA - Widya Lestari Nainggolan (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
Public understanding of the concept of Islamic finance plays an important role in increasing the use of Islamic financial products and services, particularly microfinancing targeted at small business actors. Although Indonesia is known as a country with a Muslim-majority population, the level of Islamic financial literacy remains relatively low—only 8.11% according to OJK data. Interestingly, the use of Islamic microfinancing is also found in areas where the majority of the population is non-Muslim, such as Pangaribuan District in North Tapanuli Regency. This study aims to analyze the influence of Islamic financial literacy on the level of utilization of Islamic microfinancing by non-Muslim business actors. Using a quantitative approach and a survey method involving 35 respondents, data were analyzed through validity, reliability, normality, linearity tests, and simple linear regression. The results show that Islamic financial literacy has a positive and significant effect on the use of Islamic microfinancing, highlighting the importance of improving literacy as an effort to expand Islamic financial inclusion in predominantly non-Muslim communities.